"Sobrou o apoio!" desencontro na construção da profissionalidade docente das professoras de apoio - Márcio Boaventura Júnior (2019)
A classroom permanent support teacher, in public education system of Minas Gerais, is the professional whose expertise is special education, or a teacher trained to do that job. He helps educating pupils who need intense and continuous support, assisting the main teacher and the school's teaching board. In this research we tried to watch and listen to support teatchers regarding their unique expertise and about the cloudy situation of their odd job within the school - often an awkward one both for them and for those who work with them. We have investigated - both through research and open interviews - the daily lives of those support teachers, trying to understand which positionings, conflicts and exits have they been building to deal with their work's contigencies. We have researched both theoretical referencial and collected interviews, trying to elect descriptors that would stress relevant points so we could understand if and how is this support teacher profession being build.